PENGARUH LIKUIDITAS, LEVERAGE DAN PERTUMBUHAN PERUSAHAAN TERHADAP PERINGKAT OBLIGASI - Putri Kinanti Azani; Khairunnisa khairunnisa (JAF (Journal of Accounting and Finance), 2019)
Bond rating is a risk scale which can illustrate the ability of a company in fulfilling its obligation to pay interest or pay off principal. The higher the bond rating, the more a company is considered able to fulfill its obligation punctually. Conversely, the lower the bond rating, the higher the risk of failure to pay. This study was aimed to determine factors influencing bond rate. The research variables were liquidity, leverage and company growth. The research object was bonds published by non-financial and non-banking companies rated by PT. PEFINDO in 2011-2015. The sampling technique was purposive sampling, which collected 105 bonds published by 7 companies. The data analysis model in this study was logistic regression analysis using SPSS 21 sofware. The research result showed that variables liquidity and leverage had significant positive influence on bond rating while company growth had significant negative influence on bond rating